Capacitação virtual na atenção primária em ambulatório universitário: o papel de uma instituição de ensino superior na telenfermagem - Oliva, Maria da Penha Monteiro (2015)
The use of virtual education may be applied to validated protocols and used in the nursing field and is an important tool to capacitate and enhance knowledge in primary health care of future professionals addition to identifying gaps in the realization of a particular procedure and contribute to good practices of future professionals of health services. A survey on the needs of outpatient services was employed and to answer questions about the relationship between characteristics of individuals or groups. The research strategy used was a case study with a qualitative approach, since its goal is the study of the outpatient clinic focused on teaching practice of an Institution of Higher Education. The case study as a research strategy is preferred when the focus is on contemporary phenomena inserted in a context of real life, as pointed out in this study. The evaluation of the lesson video occurred through semi-structured questionnaire administered to 200 students of third semester of the nursing course about the practice of blood pressure measurement. In order to understand how information management can contribute to student learning in nursing practice was also the focus of this study and one open interview with professional recognized expertise was held in the area of telemedicine, teleducation and telehealth. The primary objective was to create a script teleclass on the proper practice of blood pressure measurement, as part of a training applied in an outpatient clinic of an integrated higher education institution to the Unified Health System (UHS) identifying the needs of the HEI and its students, in order to establish professional practice role models associated with telehealth and propose the use of video lessons in primary care, to contribute to the improvement of teaching and professional practice (telenursing). About the knowledge of the standardization of blood pressure measurement, 70% of the 200 students referred to know the standards of the American Heart Association (AHA). As for the information provided in the video, 91.5% of the students considered enlightening. If the procedures performed in practice by professionals without proper training or knowledge of AHA standards in service of the public health system, could trigger unnecessary spending on medicines, consultations, and growing queues for the service of supposedly hypertensive individuals due to the inaccuracy of values obtained by the observer. Interactive education (IE), according to Professor Chao Lung Wen, Ph.D and coordinator and responsible for the Virtual Human Project and Media with 3D printing is still growing and promising in HEIs, with the employment resource hybrid methods of electronics and information technology resources, such as 3D computer graphics, 3D printers, educational platforms among other resources of unconventional methods.